Hospitality English: Essential Phrases for Hotel and Tourism Professionals - Marasabessy, Fachria Yamin; Amalia Mustika; Indriyani, Susi; Rizki Amelia; Ratna Rintaningrum (PT Inovasi Pratama Internasional, 2025)
English is essential in the hospitality and tourism industry as the primary communication tool between hotel staff and international guests. Effective English communication enhances service quality, guest satisfaction, and the hotel's reputation in the global market. However, many hotels in Indonesia face challenges in maintaining consistent English standards, particularly in mastering key service phrases. This study aims to identify essential phrases for hotel professionals, evaluate their effectiveness, and analyze factors influencing English proficiency in hospitality settings. A mixed-methods approach with qualitative and quantitative descriptive methods was used. Data were collected through field observations, interviews with hotel managers and staff, and guest satisfaction surveys. Findings reveal that international hotels in major cities like Jakarta and Bali exhibit higher English proficiency compared to developing hotels in cities such as Bandung, Yogyakarta, Medan, and Surabaya. Contributing factors to better English standards include regular training, the use of standardized service scripts, and a work environment that necessitates English communication. In contrast, developing hotels struggle with challenges such as limited formal training, inconsistent English use, and low staff awareness of key service phrases. To address these issues, this study recommends strategies including real-life scenario-based training programs, language learning technology integration, periodic mentoring and evaluation, and the implementation of Standard Operating Procedures (SOPs) for service communication. These strategies are expected to improve hotel service communication, enhance guest satisfaction, and strengthen Indonesia’s hotel industry competitiveness on an international scale. By prioritizing English language training, hotels can create a more professional service environment, ensuring a seamless experience for international guests and fostering a strong global reputation.